Interaction between Low Back Pain and Knee Pain – Contribution to Disability in Individuals with Knee Osteoarthritis: A Cross-Sectional Study. (Journal of Pakistan Orthopaedic Association, 2024)
Objective: The study aims to find out the association between knee pain and lower back pain.Methodology: This study focuses on a cohort of 1254 individuals who fulfilled the inclusion criteria and presented to the clinic with Knee pain from January 2022 till August 2023.Results: Majority of our patients were females (55%). 853 patients had associated lower back pain which was 68% of the total patients that presented with knee pain. There was an association of smoking (55.2%) with lower back pain and knee osteoarthritis. Most of our patients with LBP had associated moderate to severe depression, which was 79.7% according to the GDS scale. There was a significant association in ODI scores for the patients with lower back pain when comparing patients with ones without lower back pain (p-value